Comparative Genomics of Two Independently Enriched “Candidatus Kuenenia Stuttgartiensis” Anammox Bacteria - Speth, Daan R.; Hu, Baolan; Bosch, Niek; Keltjens, Jan; Stunnenberg, Hendrik; Jetten, Mike (Frontiers in Microbiology, 2012)
Bacteria capable of anaerobic oxidation of ammonium (anammox) form a deep branching clade within the Planctomycetes. Biochemical and imaging studies have elucidated the metabolism of these bacteria and revealed many unique features, such as the conversion of hydrazine, an anammoxosome compartment and ladderane lipids. Although the core metabolic pathway of anammox bacteria is largely resolved, many questions still remain. Data mining of the (meta)genomes of anammox bacteria is one of the powerful methods to address these questions or identify targets for further study. The availability of high quality reference data greatly aids such analysis. Currently, only a single ‘near complete’ (~98%) reference genome is available; that of model organism ‘Candidatus Kuenenia stuttgartiensis’. Here we present a comparative genomic analysis of two ‘Ca. K. stuttgartiensis’ anammox bacteria that were independently enriched, with the aim to understand more about the evolution, cell plan and metabolism of these important microbes and to further improve and complete the reference genome. The two anammox bacteria used are ‘Ca. K. stuttgartiensis’ RU1, which was originally sequenced for the reference genome in 2002, and for the present study resequenced after seven (2002-2009) years in continuous culture. Furthermore ‘Ca. K. stuttgartiensis’ CH1, enriched from a Chinese wastewater treatment plant was used as an independent source of genomic information. The two different ‘Ca. Kuenenia’ bacteria showed a very high sequence identity (> 99 % at nucleotide level) over the entire genome, but 31 genomic regions (average size 11 kb) were absent from strain CH1 and 220 kb of sequence was specifically found in the CH1 assembly. The high sequence homology between these two bacteria indicates that mobile genetic elements are the main source of variation between these geographically widely separated strains.